Enigma of IL-17 and Th17 Cells in Rheumatoid Arthritis and in Autoimmune Animal Models of Arthritis - Reka Kugyelka; Zoltan Kohl; Katalin Olasz; Katalin Mikecz; Tibor A. Rauch; Tibor T. Glant; Ferenc Boldizsar (Hindawi Limited, 2016)
Rheumatoid arthritis (RA) is one of the most common autoimmune disorders characterized by the chronic and progressive inflammation of various organs, most notably the synovia of joints leading to joint destruction, a shorter life expectancy, and reduced quality of life. Although we have substantial information about the pathophysiology of the disease with various groups of immune cells and soluble mediators identified to participate in the pathogenesis, several aspects of the altered immune functions and regulation in RA remain controversial. Animal models are especially useful in such scenarios. Recently research focused on IL-17 and IL-17 producing cells in various inflammatory diseases such as in RA and in different rodent models of RA. These studies provided occasionally contradictory results with IL-17 being more prominent in some of the models than in others; the findings of such experimental setups were sometimes inconclusive compared to the human data. The aim of this review is to summarize briefly the recent advancements on the role of IL-17, particularly in the different rodent models of RA.